Brain-drain and health care delivery in developing countries - Yusuf Abdu Misau; Nabilla Al-Sadat; Adamu Bakari Gerei (AOSIS, 2010)
Migration of health workers 'Brain drain' is defined as the movement of health personnel in search of a better standard of living and life quality, higher salaries, access to advanced technology and more stable political conditions in different places worldwide. The debate about migration of health workers from the developing to the developed world has remained pertinent for decades now. Regardless of the push and pull factors, migration of health care workers from developing countries to developed ones, have done more harm than good on the health care deliveries in the developing countries. This article reviews the literature on the effects of cross-border migration of health care professionals.